Electrochemical pumping: An alternative solution for hydrogen embrittlement. (December 2022) - Kim, Jinwoo; Yao, Xiahui; Kong, Decheng; Li, Ju; Yildiz, Bilge; Tasan, C. Cem
Highlights: Electrochemically biased desorption of hydrogen is proposed for preventing structural alloys from hydrogen embrittlement. The effectiveness of the method is demonstrated through proof-of-principle experiments carried out on stainless steels. The applicability and limits of the method are discussed focusing on microstructure and charging condition effects. Abstract: Hydrogen embrittlement is a form of chemo-mechanical damage that is special in that it can be partially reversible. Here, we propose a method for recovering structural alloys from hydrogen embrittlement at room temperature by electrochemically biased desorption of hydrogen. We demonstrate that the method can enable the reversion of hydrogen-induced degradation of mechanical properties, by comparing the mechanical behavior of commercial stainless steel specimens at different hydrogen charging and desorption states. These case studies also reveal the influence of electrochemical potential, H content and the characteristics of H trapping sites, on the effectiveness of this recovery approach. The limitations arising from the presence of unhealable forms of hydrogen damage, and the generic applicability of this electrochemically-assisted recovery method are also discussed. Graphical abstract: Image, graphical abstract